Peningkatan Pengetahuan dan Keterampilan Kader Posyandu dalam Pengukuran Antropometri di Kelurahan Cilandak Barat Jakarta Selatan - Anna Fitriani; Desiani Rizki Purwaningtyas (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
The low knowledge and skills of posyandu cadres in anthropometric measurements, from installing and measuring measuring instruments, weighing, measuring body length and height of toddlers to recording measurement results have an impact on inaccurate data collection and reporting of nutritional status. One of the contributing factors is the lack of counseling and training for posyandu cadres. Therefore, this community partnership program (PKM) provides solutions in the form of counseling and training on anthropometric measurements for posyandu cadres in West Cilandak Village. The knowledge and skills of cadres before and after the intervention were measured. The results of the analysis showed a significant increase in the average score of knowledge (11.13 to 14.67) and skills score (26.59 to 39.00) (p value = 0.001). This shows that counseling and training are effective in increasing the knowledge and skills of posyandu cadres.